PENGELOLAAN KAS DAN SETARA KAS YANG OPTIMAL DALAM RANGKA MENINGKATKAN PROFITABILITAS PADA PT. SELECTA BATU - Rachman, Ady Warsito; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Cash management includes the efficient collection, payment of cash and temporary investments in marketable securities. This study aims to determine the management of cash and cash equivalents in order to improve profitability in the PT Selecta and whether management of cash and cash equivalents are carried out is optimal. Object of this study is the PT Selecta Batu. The results showed, cash management and cash equivalents are carried out by PT Selecta has not been optimal. In 2011, when the company's liquidity is high due to large cash holdings, cash turnover actually decreased from the previous year. That is because the PT Selecta has not been idle cash invested in marketable securities, so that the profit earned is not maximized. To obtain optimality in cash management, investing idle cash can be made through securities firms, one of which is the product of PT Danareksa Sekuritas, Reksa Dana Seruni Pasar Uang III that has a consistent level of return ride. Keyword : Cash Management, Idle Cash, Securities, Cash Inflow, Cash Outflow.